“Evaluation Of Bite Force And Its Corelation With Skeletal Malocclusions – An In Vivo Study” - Bhardwaj, Madhvi; Chauhan, Ashish; Gupta, Sweety; Pandey, Aisshanya; Sahu, Kanchan; Dagdiya, Manish (Journal of Neonatal Surgery, 2025)
Introduction: Maximum bite force (MBF) refers to the greatest force generated by the masticatory system during functional contact. It serves as a key indicator of the functional capacity of the stomatognathic system and reflects the efficiency of the masticatory apparatus. Aim : The present study aimed to compare maximum bite force among individuals with different sagittal malocclusions. Methodology : Patients reporting to the Department of Orthodontics and Dentofacial orthopaedics’ at Saraswati Dental College were recruited for the study. Participants were classified into three groups based on skeletal (Class I, Class II and Class III) malocclusion. Maximum bite force was measured using a digital bite force transducer, expressed in Newton’s, and the data were subjected to statistical analysis. Result : A decreasing trend in maximum bite force was observed across the groups, with the highest values recorded in Class I malocclusion and the lowest in Class III malocclusion. Conclusion : Within the limitations of this study, it can be concluded that subjects with Class I malocclusion exhibit greater maximum bite force, suggesting a more efficient masticatory system and improved chewing efficiency compared to those with Class II and Class III malocclusions..